Composite lithium-supplementing negative electrode plate, preparation method thereof and lithium ion battery
By using a composite lithium supplementary negative electrode sheet on the negative electrode sheet of the lithium-ion battery, and using a blend layer of liquid metal lithium material and conductive material, the irreversible lithium ion loss problem of the lithium-ion battery during the first charge is solved, and the safety and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202311121476.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
Existing lithium-ion batteries will have irreversible lithium-ion losses when charged for the first time, resulting in a reduced battery efficiency and affecting capacity and energy density. At the same time, the method of lithium supplementation for negative electrodes has problems such as poor uniformity, low safety and complex process.
A composite lithium supplement negative electrode sheet is used, which includes a negative current collector, a negative electrode active material layer and a lithium supplement layer. The lithium replenishing layer consists of a blended material of liquid metal lithium material, a lithium replenishing conductive material, a lithium replenishing binder and a passivation material. It is obtained by drying rolling and is loaded on the negative electrode active material layer.
It improves the uniformity and stability of lithium supplement materials, reduces the formation of lithium dendrites, improves the safety and electrochemical performance of the battery, and improves the first-time Coulomb efficiency and cycle stability.
Smart Images

Figure CN119542354A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a composite lithium-supplementing negative electrode sheet and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries are currently widely used in various electronic devices and electric energy storage devices. When a lithium-ion battery is charged for the first time, the lithium ions released from the positive electrode will have a certain amount of irreversible lithium loss at the negative electrode due to the formation of a solid electrolyte interface (SE I) film, which will lead to a decrease in the initial efficiency of the battery and affect the battery capacity and energy density.
[0003] In order to improve the initial efficiency of the battery, the industry generally adopts the method of lithium replenishment to make up for the above irreversible lithium loss. The methods of lithium replenishment are mainly divided into positive electrode lithium replenishment and negative electrode lithium replenishment. The typical positive electrode lithium replenishment is to add a small amount of high-capacity material during the positive electrode slurry process. During the charging process, Li + The high-capacity material is extracted to make up for the irreversible capacity loss of the first charge and discharge. However, the realization of positive electrode lithium replenishment may increase the complexity of the preparation process and may require the redesign of the battery structure to accommodate the addition of lithium replenishment materials.
[0004] At present, the methods of replenishing lithium at the negative electrode are relatively common, mainly the following:
[0005] 1) Directly press the lithium foil into thin sheets and attach them to the surface of the negative electrode. This method is very easy to generate heat and has high requirements on the environment.
[0006] 2) Lithium powder is mixed with a binder and then applied to the negative electrode surface, or lithium powder is mixed with negative electrode slurry and then applied to the current collector. However, lithium powder is difficult to disperse evenly and is prone to agglomeration, which makes it easier to form lithium dendrites and bring safety risks.
[0007] Therefore, how to improve the lithium replenishment effect of the negative electrode plate, improve the electrochemical performance of the battery, ensure the safety of the lithium replenishment process, and simplify the lithium replenishment process is a technical problem that needs to be solved urgently. Summary of the invention
[0008] The purpose of the present invention is to provide a composite lithium-supplemented negative electrode sheet and a preparation method thereof and a lithium-ion battery. The present invention can improve the uniformity and stability of the lithium-supplemented material, reduce the formation of negative electrode lithium dendrites and improve safety, and improve the first coulombic efficiency and enhance the electrochemical performance.
[0009] To this end, in a first aspect, an embodiment of the present invention provides a composite lithium-supplemented negative electrode sheet, comprising: a negative electrode current collector, a negative electrode active material layer and a lithium-supplemented layer;
[0010] The lithium supplement layer is obtained by drying and rolling a mixed material of liquid metal lithium material, lithium supplement conductive material, lithium supplement binder, and passivation material; the lithium supplement layer is loaded on the negative electrode active material layer, and the negative electrode active material layer is loaded on the current collector;
[0011] The liquid metal lithium material is a mixed material of metal lithium, aromatic compounds and ether organic solvents.
[0012] Preferably, the metallic lithium comprises: a combination of one or more of metallic lithium strips, metallic lithium powders, and metallic lithium sheets;
[0013] The aromatic compound includes: biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives or a combination of one or more thereof;
[0014] The ether solvent includes: diethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, ethylene oxide, propylene oxide, or any one or more combinations thereof;
[0015] The lithium-supplementing conductive material includes: multi-walled carbon nanotubes;
[0016] The lithium supplement binder comprises: polytetrafluoroethylene;
[0017] The passivation material includes: a combination of one or more of nano-aluminum oxide and nano-silicon dioxide.
[0018] Preferably, the negative electrode current collector is copper foil;
[0019] The negative electrode active material layer comprises: a negative electrode active material, a negative electrode conductive material, and a negative electrode binder;
[0020] Among them, the negative electrode active material includes: a combination of one or more of nano silicon powder, micron silicon powder, silicon-carbon material, natural graphite, artificial graphite, and hard carbon; the negative electrode conductive material includes: a combination of one or more of conductive carbon black, conductive graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; the negative electrode binder includes: a combination of one or more of polytetrafluoroethylene (PVDF), polyacrylic acid (PAA), sodium alginate (SA), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).
[0021] Further preferably, the mass ratio of the negative electrode active material, the negative electrode conductive material and the negative electrode binder is 92% to 97%: 1.5% to 4%: 1.5% to 4%.
[0022] Preferably, the mass ratio of the liquid metal lithium material, the lithium-supplementing conductive material, the lithium-supplementing binder and the passivation material is 50-80:8-20:8-20:4-10.
[0023] In a second aspect, an embodiment of the present invention provides a method for preparing the composite lithium-supplementing negative electrode sheet according to the first aspect, comprising:
[0024] The negative electrode active material, the negative electrode conductive material and the negative electrode binder are mixed according to a mass ratio and added into deionized water, and dispersed evenly to obtain a negative electrode active material slurry;
[0025] Applying the negative electrode active material slurry on the negative electrode current collector and drying to obtain a negative electrode sheet;
[0026] Dissolving metallic lithium and aromatic compounds in an ether organic solvent according to a mass ratio under an inert environment to obtain a liquid metallic lithium material, and then adding a lithium-replenishing conductive material, a lithium-replenishing binder and a passivating substance, and dispersing them to obtain a lithium-replenishing layer slurry;
[0027] The lithium supplement layer slurry is coated on the negative electrode sheet in an inert environment, and then vacuum dried and rolled to obtain the composite lithium supplement negative electrode sheet.
[0028] Preferably, the mass ratio of the negative electrode active material, the negative electrode conductive material and the negative electrode binder is 92% to 97%: 1.5% to 4%: 1.5% to 4%;
[0029] The viscosity of the negative electrode active material slurry is 1500-3500 mPa·s, and the solid content is 45%-50%;
[0030] The negative electrode current collector is copper foil with a thickness of 6 to 12 μm;
[0031] The coating surface density of the negative electrode active material slurry on the negative electrode current collector is 88 to 108 g / m 2 , coating thickness is 130~150μm;
[0032] The drying temperature is 85-110° C., and the drying time is 0.5-2 h.
[0033] Preferably, the inert environment is a nitrogen environment or an argon environment;
[0034] The mass ratio of the metallic lithium to the aromatic compound is 2:8-5:5;
[0035] In the lithium replenishment layer slurry, the mass ratio of the liquid metal lithium material, the lithium replenishment conductive material, the lithium replenishment binder and the passivation material is 50-80:8-20:8-20:4-10;
[0036] The viscosity of the lithium supplementation layer slurry is 5000-12000 mPa·s, and the solid content is 55%-75%;
[0037] The coating thickness of the lithium supplement layer slurry on the negative electrode sheet is 1 to 10 μm; the vacuum drying temperature is 80 to 100° C., and the vacuum drying time is 0.5 to 1 hour.
[0038] In a third aspect, an embodiment of the present invention provides a lithium-ion battery, comprising: a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet is the composite lithium-supplementing negative electrode sheet described in the first aspect above.
[0039] The composite lithium-supplementing negative electrode sheet provided by the embodiment of the present invention has a liquid lithium metal material formed by dissolving lithium metal in aromatic compounds and ether solvents, which has better uniformity and better conductivity after being mixed with a conductive material to form a conductive network; after adding a binder to form a slurry and coating it on the negative electrode active material layer, it is more tightly combined with the negative electrode active material, and the lithium-supplementing effect is better and the ion and electron conduction is better; after adding nano-oxide as a passivation material, a stable oxide film is formed on the surface of the lithium metal to protect the lithium metal material, thereby improving the stability of the lithium metal in the air, thereby further improving the safety and air stability of the lithium-supplementing negative electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A schematic diagram of a composite lithium-supplementing negative electrode sheet provided in an embodiment of the present invention;
[0041] Figure 2 A flow chart of a method for preparing a composite lithium-supplementing negative electrode sheet provided in an embodiment of the present invention;
[0042] Figure 3 The 100-cycle retention rate curve of Example 2 of the present invention and Comparative Example 2 is shown. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0044] The embodiment of the present invention provides a composite lithium supplement negative electrode sheet, such as Figure 1 As shown, it includes: a negative electrode current collector, a negative electrode active material layer and a lithium supplement layer;
[0045] The negative electrode current collector is a copper foil, and the thickness of the copper foil is preferably 6 to 12 μm.
[0046] The negative electrode active material layer is loaded on the current collector, and includes: negative electrode active material, negative electrode conductive material, and negative electrode binder; wherein the negative electrode active material includes: one or more combinations of nano silicon powder, micro silicon powder, silicon carbon material, natural graphite, artificial graphite, and hard carbon; the negative electrode conductive material includes: one or more combinations of conductive carbon black, conductive graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; the negative electrode binder includes: one or more combinations of polytetrafluoroethylene (PVDF), polyacrylic acid (PAA), sodium alginate (SA), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). The mass ratio of the negative electrode active material, the negative electrode conductive material, and the negative electrode binder is 92% to 97%: 1.5% to 4%: 1.5% to 4%.
[0047] The lithium supplement layer is obtained by drying and rolling a mixed material of a liquid metal lithium material, a lithium supplement conductive material, a lithium supplement binder, and a passivation material; the lithium supplement layer is loaded on the negative electrode active material layer. The mass ratio of the liquid metal lithium material, the lithium supplement conductive material, the lithium supplement binder, and the passivation material is 50-80:8-20:8-20:4-10.
[0048] Among them, the liquid metal lithium material is a blend of metal lithium, aromatic compounds and ether organic solvents. Metal lithium includes: a combination of one or more of metal lithium strips, metal lithium powders and metal lithium sheets; aromatic compounds include: a combination of one or more of biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives; ether solvents include: ethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, ethylene oxide, propylene oxide, any one or more of the combinations.
[0049] The lithium-supplementing conductive material includes: multi-walled carbon nanotubes; the lithium-supplementing binder includes: polytetrafluoroethylene; the passivation material includes: a combination of one or more of nano-alumina and nano-silicon dioxide.
[0050] In the lithium replenishment layer, liquid metal lithium material is the lithium replenishment source in the battery. During the battery cycle, lithium ions will gradually migrate to the positive electrode of the battery, causing the negative electrode to lose some lithium ions, thereby reducing the battery capacity and cycle life. Liquid metal lithium can release lithium ions during the charge and discharge process of the battery to replenish the lithium loss on the negative electrode, thereby extending the service life and stability of the battery. The lithium replenishment layer needs to have good conductivity so that the current can be smoothly transmitted during the charge and discharge process of the battery. The lithium replenishment conductive material plays a conductive role in the lithium replenishment layer and enhances the transfer of lithium ions. The lithium replenishment binder is used to stably bond the various components in the lithium replenishment layer together. During the charge and discharge process of the battery, the lithium replenishment layer needs to maintain structural stability to ensure that the various materials will not separate or peel off. During the operation of the battery, liquid metal lithium may undergo unnecessary chemical reactions with other materials, resulting in a decrease in battery performance or even damage. The passivation material does not participate in the electrochemical reaction but can form a protective oxide film on the surface of the lithium replenishment layer to reduce the reaction with other materials, thereby improving the stability and durability of the battery. Therefore, the liquid metal lithium material in the lithium replenishment layer provides lithium ions, the lithium replenishment conductive material improves the electrical performance, the lithium replenishment binder maintains structural stability, and the passivation material protects the negative electrode material from unnecessary reactions, further improving the safety and air stability of the lithium replenishment negative electrode sheet, thereby working together to improve the performance of lithium-ion batteries.
[0051] The composite lithium supplement negative electrode sheet of the present invention can be prepared by Figure 2 The preparation method is prepared by the following main steps:
[0052] Step 110, mixing the negative electrode active material, the negative electrode conductive material and the negative electrode binder according to a mass ratio, adding them into deionized water, and dispersing them evenly to obtain a negative electrode active material slurry;
[0053] The mass ratio of the negative electrode active material, the negative electrode conductive material and the negative electrode binder is 92% to 97%: 1.5% to 4%: 1.5% to 4%; the viscosity of the negative electrode active material slurry is 1500 to 3500 mPa·s, and the solid content is 45% to 50%.
[0054] Specifically, the mass proportion of the negative electrode active material in the above-mentioned negative electrode active material slurry is 92-97%, for example, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%; the mass proportion of the negative electrode conductive material is 1.5-4%, for example, 1.5%, 1.8%, 2.1%, 2.4%, 2.7%, 3%, 3.3%, 3.6%, 3.8%, 4%; the mass proportion of the negative electrode binder is 1.5-4%, for example, 1.5%, 1.8%, 2.1%, 2.4%, 2.7%, 3%, 3.3%, 3.6%, 3.8%, 4%.
[0055] The viscosity of the negative electrode active material slurry is 1500-3500 mPa·s, for example, 1500 mPa·s, 1600 mPa·s, 1800 mPa·s, 2000 mPa·s, 2200 mPa·s, 2400 mPa·s, 2600 mPa·s, 2800 mPa·s, 3000 mPa·s, 3200 mPa·s, 3500 mPa·s; the solid content is 45%-50%, for example, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%.
[0056] Step 120, coating the negative electrode active material slurry on the negative electrode current collector, and drying to obtain a negative electrode sheet;
[0057] The negative electrode current collector is copper foil with a thickness of 6 to 12 μm; the coating surface density of the negative electrode active material slurry on the negative electrode current collector is 88 to 108 g / m 2 The coating thickness is 130-150 μm; the drying temperature is 85-110°C, and the drying time is 0.5-2 h.
[0058] Specifically, the thickness of the copper foil is 6 to 12 μm, for example, 6 μm, 8 μm, 10 μm, or 12 μm; the coating surface density is 88 to 108 g / m 2 , for example 88g / m 2 , 90g / m 2 , 92g / m 2 , 94g / m 2 , 96g / m 2 , 98g / m 2 , 100g / m 2 , 102g / m 2 , 104g / m 2 , 106g / m 2 , 108g / m 2 ; The coating thickness is 130-150μm, for example, 130μm, 134μm, 138μm, 142μm, 146μm, and 150μm; the drying temperature is 85-110℃, for example, 85℃, 88℃, 90℃, 94℃, 98℃, 102℃, 106℃, and 110℃; the drying time is 0.5-2h, for example, 0.5h, 0.8h, 1.1h, 1.4h, 1.7h, and 2h.
[0059] Step 130, dissolving metallic lithium and aromatic compounds in an ether organic solvent in an inert environment according to a mass ratio to obtain a liquid metallic lithium material, and then adding a lithium replenishing conductive material, a lithium replenishing binder and a passivating substance to obtain a lithium replenishing layer slurry after dispersion;
[0060] Preferably, the inert environment is a nitrogen environment or an argon environment; more preferably, an argon environment.
[0061] The mass ratio of metallic lithium to aromatic compounds is 2:8-5:5, that is, the mass ratio of metallic lithium material is 20%-50%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%; the mass ratio of aromatic compounds is 50%-80%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%.
[0062] In the lithium replenishing layer slurry, the mass ratio of liquid metal lithium material, lithium replenishing conductive material, lithium replenishing binder and passivation material is 50-80:8-20:8-20:4-10; for example, the mass ratio of metal lithium material can be 50%, 54%, 58%, 60%, 62%, 66%, 70%, 72%, 74%, 76%, 80%; the mass ratio of conductive material can be 8%, 10%, 12%, 14%, 16%, 18%, 20%; the mass ratio of binder can be 8%, 10%, 12%, 14%, 16%, 18%, 20%; the mass ratio of passivation material can be 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0063] The viscosity of the lithium replenishing layer slurry is 5000-12000mPa·s, for example, 5000mPa·s, 6000mPa·s, 7000mPa·s, 8000mPa·s, 9000mPa·s, 10000mPa·s, 11000mPa·s, 12000mPa·s; the solid content is 55%-75%, for example, 55%, 58%, 62%, 65%, 68%, 72%, 75%.
[0064] Step 140, coating the lithium supplement layer slurry on the negative electrode sheet in an inert environment, vacuum drying and rolling to obtain a composite lithium supplement negative electrode sheet.
[0065] Specifically, the coating thickness of the lithium replenishing layer slurry on the negative electrode sheet is 1 to 10 μm, for example, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, and 10 μm; the vacuum drying temperature is 80 to 100°C, for example, 80°C, 84°C, 88°C, 92°C, 96°C, and 100°C; the vacuum drying time is 0.5 to 1 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, and 1 h.
[0066] The composite lithium-supplementing negative electrode sheet of the present invention can be applied to lithium-ion batteries. For example, the composite lithium-supplementing negative electrode sheet prepared by the method of the present invention is matched with a mature lithium manganese oxide positive electrode sheet to prepare a soft-pack full battery.
[0067] The composite lithium-supplementing negative electrode sheet provided by the embodiment of the present invention has a liquid lithium metal material formed by dissolving lithium metal in aromatic compounds and ether solvents, which has better uniformity and better conductivity after being mixed with a conductive material to form a conductive network; after adding a binder to form a slurry and coating it on the negative electrode active material layer, it is more tightly combined with the negative electrode active material, and the lithium-supplementing effect is better and the ion and electron conduction is better; after adding nano-oxide as a passivation material, the lithium metal material is protected and the stability of the lithium metal in the air is improved, thereby further improving the safety and air stability of the lithium-supplementing negative electrode sheet.
[0068] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0069] Example 1
[0070] Step 1, add 1.06Kg of polyacrylic acid and 2.33Kg of deionized water into a high-speed stirring tank, stir for 10 minutes at a revolution of 10r / min and a rotation of 500r / min, then increase the speed to 16r / min of revolution and 1000r / min of rotation and stir for 20 minutes, then add 0.028Kg of conductive carbon black and 2.3Kg of artificial graphite, and continue stirring for 60 minutes at a revolution of 16r / min and a rotation of 1000r / min, then add 1.7Kg of deionized water and continue stirring for 30 minutes to adjust the viscosity, to obtain a negative electrode slurry with a viscosity of 3100mPa·s and a solid content of 45.6%.
[0071] Step 2: Apply the negative electrode slurry on a 6 μm copper foil with a coating surface density of 99 g / m 2 The coating thickness is 134 μm, and the negative electrode sheet is obtained after drying at 90°C for 1.5 h.
[0072] Step 3, adding 300g of tetrahydrofuran and 180g of biphenyl to 100g of metallic lithium powder in a high-speed stirring tank, stirring for 8min at a revolution speed of 12r / min and a rotation speed of 700r / min to form a metallic lithium solution; then adding 16g of multi-walled carbon nanotubes, 16g of polytetrafluoroethylene and 8g of nano-silicon dioxide to the metallic lithium solution, increasing the speed to revolution 15r / min and rotation 1500r / min, stirring for 5min to fully mix, and finally adding a small amount of tetrahydrofuran and continuing to stir for 5min to adjust the viscosity to obtain a lithium supplement layer slurry with a viscosity of 10000mPa·s and a solid content of 56%.
[0073] Step 4: Apply the lithium supplement layer slurry on the negative electrode sheet with a coating thickness of 2 μm, and then dry it at 80°C for 0.6 h and roll it on a roller press to obtain a compaction density of 1.49 g / cm 3 Composite lithium-supplemented negative electrode sheet.
[0074] Step 5: assemble the above-mentioned composite lithium-supplementing negative electrode sheet with NCM523 into a 1Ah soft-pack lithium-ion battery.
[0075] Example 2
[0076] Step 1, add 1.21Kg of aqueous binder slurry and 3.65Kg of deionized water into a high-speed stirring tank, stir for 12 minutes at a revolution of 10r / min and a rotation of 550r / min, then increase the speed to 15r / min and 1000r / min and stir for 20 minutes, then add 0.182Kg of conductive carbon black and 8.4Kg of silicon-carbon material, and continue stirring for 60 minutes at a revolution of 16r / min and a rotation of 1000r / min, then add 6.3Kg of deionized water and continue stirring for 30 minutes to adjust the viscosity to obtain a negative electrode slurry with a viscosity of 2800mPa·s and a solid content of 46.6%.
[0077] Step 2: coat the negative electrode slurry on 8 μm copper foil with a coating surface density of 106 g / m 2 The coating thickness is 138 μm, and the negative electrode sheet is obtained after drying at 88°C for 2 h.
[0078] Step 3, adding 480g of ether and 320g of naphthalene to 80g of lithium metal sheets in a high-speed stirring tank, stirring for 8min at a revolution speed of 10r / min and a rotation speed of 700r / min to form a lithium metal solution; then adding 15g of multi-walled carbon nanotubes, 14g of polytetrafluoroethylene and 5.8g of nano-silicon dioxide to the lithium metal solution, increasing the speed to revolution 15r / min and rotation 1500r / min, stirring for 5min to fully mix, and finally adding a small amount of ether and continuing to stir for 5min to adjust the viscosity, to obtain a lithium supplement layer slurry with a viscosity of 12000mPa·s and a solid content of 55%.
[0079] Step 4: Apply the lithium supplement layer slurry on the negative electrode sheet with a coating thickness of 1 μm; then dry it at 84°C for 0.7h and roll it on a roller press to obtain a compaction density of 1.46 g / cm 3 Composite lithium-supplemented negative electrode sheet.
[0080] Step 5: assemble the above-mentioned composite lithium-supplementing negative electrode sheet with NCM523 into a 1Ah soft-pack lithium-ion battery.
[0081] Example 3
[0082] Step 1, add 1.5Kg of sodium alginate and 25.5Kg of deionized water into a high-speed stirring tank, stir for 10 minutes at a revolution of 10r / min and a rotation of 600r / min, then increase the speed to 16r / min and 1000r / min and stir for 20 minutes, then add 1.5Kg of conductive graphite and 97Kg of micron silicon powder, and continue stirring for 60 minutes at a revolution of 16r / min and a rotation of 1000r / min, then add 50.7Kg of deionized water and continue stirring for 30 minutes to adjust the viscosity, and obtain a negative electrode slurry with a viscosity of 3000mPa·s and a solid content of 45.8%.
[0083] Step 2: Coat the negative electrode slurry on 8 μm copper foil with a coating surface density of 105 g / m 2 The coating thickness is 140 μm, and the negative electrode sheet is obtained after drying at 90°C for 1.3 h.
[0084] Step 3, add 600g of ethylene glycol dimethyl ether and 225g of biphenyl to 150g of lithium metal strip in a high-speed stirring tank, and stir for 8min at a revolution speed of 12r / min and a rotation speed of 700r / min to form a lithium metal solution; then add 22g of multi-walled carbon nanotubes, 24g of polytetrafluoroethylene and 10.4g of nano-alumina to the lithium metal solution, increase the speed to revolution 15r / min and rotation 1500r / min, and stir for 5min to fully mix, and finally add a small amount of ethylene glycol dimethyl ether and continue stirring for 5min to adjust the viscosity to obtain a lithium supplement layer slurry with a viscosity of 11050mPa·s and a solid content of 62%.
[0085] Step 4: Apply the lithium supplement layer slurry on the negative electrode sheet with a coating thickness of 4 μm; then dry it at 84°C for 0.8 h and roll it on a roller press to obtain a compaction density of 1.52 g / cm 3 Composite lithium-supplemented negative electrode sheet.
[0086] Step 5: assemble the above-mentioned composite lithium-supplementing negative electrode sheet with NCM523 into a 1Ah soft-pack lithium-ion battery.
[0087] Comparative Example 1
[0088] An artificial graphite negative electrode sheet was prepared according to the preparation method of step 1 and step 2 of implementation 1, and matched with NCM523 to be assembled into a 1Ah soft-pack lithium-ion battery.
[0089] Comparative Example 2
[0090] A silicon-carbon material negative electrode sheet was prepared according to the preparation method of step 1 and step 2 of implementation 2, and matched with NCM523 to be assembled into a 1Ah soft-pack lithium-ion battery.
[0091] Comparative Example 3
[0092] A micron silicon negative electrode sheet was prepared according to the preparation method of step 1 and step 2 of implementation 3, and matched with NCM523 to be assembled into a 1Ah soft-pack lithium-ion battery.
[0093] After the composite lithium-supplemented negative electrode sheet of the above embodiment and the negative electrode sheet of the comparative example were matched with the ternary positive electrode sheet to be assembled into a soft-pack lithium-ion battery, a cycle test was carried out at a current density of 1C in the voltage range of 2.7 to 4.2 V. The test results of the capacity retention rate after 100 cycles and the coulombic efficiency in the first week are shown in Table 1.
[0094] First week coulomb efficiency 100-week capacity retention rate Example 1 87.21% 99.79% Example 2 84.11% 96.33% Example 3 82.35% 88.31% Comparative Example 1 85.39% 98.13% Comparative Example 2 82.56% 93.60% Comparative Example 3 79.85% 80.12%
[0095] Table 1
[0096] It can be seen from the above table:
[0097] Compared with comparative examples 1-3, embodiments 1-3 have better first effect and cycle stability, and the electrochemical performance is significantly improved.
[0098] According to Table 1 and Figure 3 From the results of the cycle retention rate of 100 weeks at a current density of 1C shown in the figure, it can be seen that the highly uniform liquid metal lithium material obtained by blending the metal lithium material, aromatic compounds and ether organic solvents has better conductivity after being mixed with the conductive material to form a conductive network; after adding the binder to form a slurry and coating it on the negative electrode active material layer, it is more tightly combined with the negative electrode active material, and the lithium replenishment effect is better and the ion and electron conduction is better. The technical solution of the present invention can effectively improve the lithium replenishment performance of metal lithium, thereby improving the various electrochemical properties of traditional negative electrode materials. At the same time, the introduction of the passivation material can improve the stability of the metal lithium replenishment layer, effectively improve the preparation yield of the composite lithium replenishment negative electrode sheet, and reduce the requirements for the process.
[0099] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A composite lithium-supplemented negative electrode sheet, characterized in that: The composite lithium-supplementing negative electrode sheet comprises: a negative electrode current collector, a negative electrode active material layer and a lithium-supplementing layer; The lithium supplement layer is obtained by drying and rolling a mixed material of liquid metal lithium material, lithium supplement conductive material, lithium supplement binder, and passivation material; the lithium supplement layer is loaded on the negative electrode active material layer, and the negative electrode active material layer is loaded on the current collector; The liquid metal lithium material is a mixed material of metal lithium, aromatic compounds and ether organic solvents.
2. The composite lithium-supplementing negative electrode sheet according to claim 1, characterized in that: The metal lithium comprises: a combination of one or more of metal lithium strips, metal lithium powder and metal lithium sheets; The aromatic compound includes: biphenyl, biphenyl derivatives, naphthalene, naphthalene derivatives, anthracene or anthracene derivatives or a combination of one or more thereof; The ether solvent includes: diethyl ether, methyl ether, ethylene glycol dimethyl ether, dipropyl ether, diisopropyl ether, ethyl butyl ether, dibutyl ether, diamyl ether, diisoamyl ether, dihexyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, dimethoxymethane, ethylene oxide, propylene oxide, or any one or more combinations thereof; The lithium-supplementing conductive material includes: multi-walled carbon nanotubes; The lithium supplement binder comprises: polytetrafluoroethylene; The passivation material includes: a combination of one or more of nano-aluminum oxide and nano-silicon dioxide.
3. The composite lithium-supplementing negative electrode sheet according to claim 1, characterized in that: The negative electrode current collector is copper foil; The negative electrode active material layer comprises: a negative electrode active material, a negative electrode conductive material, and a negative electrode binder; Among them, the negative electrode active material includes: a combination of one or more of nano silicon powder, micron silicon powder, silicon-carbon material, natural graphite, artificial graphite, and hard carbon; the negative electrode conductive material includes: a combination of one or more of conductive carbon black, conductive graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; the negative electrode binder includes: a combination of one or more of polytetrafluoroethylene (PVDF), polyacrylic acid (PAA), sodium alginate (SA), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).
4. The composite lithium-supplementing negative electrode sheet according to claim 3, characterized in that: The mass ratio of the negative electrode active material, the negative electrode conductive material and the negative electrode binder is 92% to 97%: 1.5% to 4%: 1.5% to 4%.
5. The composite lithium-supplementing negative electrode sheet according to claim 1, characterized in that: The mass ratio of the liquid metal lithium material, the lithium-supplementing conductive material, the lithium-supplementing binder and the passivation material is 50-80:8-20:8-20:4-10.
6. A method for preparing the composite lithium-supplemented negative electrode sheet according to any one of claims 1 to 5, characterized in that: The preparation method comprises: The negative electrode active material, the negative electrode conductive material and the negative electrode binder are mixed according to a mass ratio and added into deionized water, and dispersed evenly to obtain a negative electrode active material slurry; Applying the negative electrode active material slurry on the negative electrode current collector and drying to obtain a negative electrode sheet; Dissolving metallic lithium and aromatic compounds in an ether organic solvent according to a mass ratio under an inert environment to obtain a liquid metallic lithium material, and then adding a lithium-replenishing conductive material, a lithium-replenishing binder and a passivating substance, and dispersing them to obtain a lithium-replenishing layer slurry; The lithium supplement layer slurry is coated on the negative electrode sheet in an inert environment, and then vacuum dried and rolled to obtain the composite lithium supplement negative electrode sheet.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the negative electrode active material, the negative electrode conductive material and the negative electrode binder is 92% to 97%: 1.5% to 4%: 1.5% to 4%; The viscosity of the negative electrode active material slurry is 1500-3500 mPa·s, and the solid content is 45%-50%; The negative electrode current collector is copper foil with a thickness of 6 to 12 μm; The coating surface density of the negative electrode active material slurry on the negative electrode current collector is 88 to 108 g / m 2 , coating thickness is 130~150μm; The drying temperature is 85-110° C., and the drying time is 0.5-2 h.
8. The preparation method according to claim 6, characterized in that: The inert environment is a nitrogen environment or an argon environment; The mass ratio of the metallic lithium to the aromatic compound is 2:8-5:5; In the lithium replenishment layer slurry, the mass ratio of the liquid metal lithium material, the lithium replenishment conductive material, the lithium replenishment binder and the passivation material is 50-80:8-20:8-20:4-10; The viscosity of the lithium supplementation layer slurry is 5000-12000 mPa·s, and the solid content is 55%-75%; The coating thickness of the lithium supplement layer slurry on the negative electrode sheet is 1 to 10 μm; the vacuum drying temperature is 80 to 100° C., and the vacuum drying time is 0.5 to 1 hour.
9. A lithium ion battery comprising: A positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the negative electrode sheet is a composite lithium-supplementing negative electrode sheet as described in any one of claims 1 to 5.